Biotechnological challenges: The scope of genome editing - Lima, Natacha Salomé (2021)
CRISPR/Cas9 can be considered as the biotechnological breakthrough of the century. Genome editing technologies have developed in a vertiginous way. While the genome editing of species, including animals, plants and bacteria has become a commonly used method, the application of CRISPR-Cas9 in human embryos has led to debates and in-terdisciplinary discussions. This brings multiple challenges for both scientists and those who must regulate the use of these techniques.